2015
DOI: 10.1089/dia.2014.0315
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Myostimulation (EMS) Improves Glucose Metabolism and Oxygen Uptake in Type 2 Diabetes Mellitus Patients—Results from the EMS Study

Abstract: EMS can improve glucose metabolism and functional performance in T2DM patients. These data suggest that EMS might emerge as a novel additional therapeutic mode of exercise training and might help patients to overcome their sedentary lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 41 publications
0
47
1
3
Order By: Relevance
“…NMES metabolic effects include improvements in whole-body glucose uptake and lower glucose levels in healthy (Hamada et al, 2004) and diabetic individuals (Miyamoto et al, 2012;Van Buuren et al, 2015). In the same way, NMES has also been shown to improve insulin sensitivity in patients with type 2 diabetes (Joubert et al, 2014), and to decrease IL-6 in patients with fatty liver disease (Kawaguchi et al, 2011).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…NMES metabolic effects include improvements in whole-body glucose uptake and lower glucose levels in healthy (Hamada et al, 2004) and diabetic individuals (Miyamoto et al, 2012;Van Buuren et al, 2015). In the same way, NMES has also been shown to improve insulin sensitivity in patients with type 2 diabetes (Joubert et al, 2014), and to decrease IL-6 in patients with fatty liver disease (Kawaguchi et al, 2011).…”
mentioning
confidence: 96%
“…In the same way, NMES has also been shown to improve insulin sensitivity in patients with type 2 diabetes (Joubert et al, 2014), and to decrease IL-6 in patients with fatty liver disease (Kawaguchi et al, 2011). In addition, increased oxygen demand, increased cardiorespiratory capacity, and decreased HbA1c levels have been observed after NMES training in diabetic patients (Van Buuren et al, 2015). Nevertheless, the current characteristics that generate the strongest hypoglycemic effect are not clear, and more particularly so for stimulation frequency (Hamada et al, 2004;Miyamoto et al, 2012;Van Buuren et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Balance can also be improved by whole-body vibration training. ▪ Initial studies indicate that additional alternative forms of training such as electrical muscle stimulation training (EMS training), whole-body vibration training or sports with interactive computer consoles (exergaming) can also achieve positive effects in patients with type 2 diabetes, including those on glycemic values, when properly supervised [38][39][40], although the effectiveness compared to classic endurance/ strength training must be evaluated in future studies. Currently, diabetes mellitus is considered a contraindication for EMS training in the commercial setting [41].…”
Section: Opportunities and Possibilities Of The Digital World In The mentioning
confidence: 99%
“…It was shown that NMES could substantially enhance energy consumption, carbohydrate oxidation, and whole body glucose uptake [8]. Moreover, NMES improved insulin sensitivity [9] or glucose metabolism [10] in people with type 2 diabetes. The combined application of electrical stimulation (ES) and volitional contractions (VC) is shown to be more effective than ES or VC alone [11,12].…”
Section: Introductionmentioning
confidence: 99%